2023
DOI: 10.3389/fphar.2023.1272969
|View full text |Cite
|
Sign up to set email alerts
|

The Nociceptin/Orphanin FQ peptide receptor antagonist, SB-612111, improves cerebral blood flow in a rat model of traumatic brain injury

Omar N. Al Yacoub,
Stefano Tarantini,
Yong Zhang
et al.

Abstract: Traumatic brain injury (TBI) affects more than 2.5 million people in the U.S. each year and is the leading cause of death and disability in children and adults ages 1 to 44. Approximately 90% of TBI cases are classified as mild but may still lead to acute detrimental effects such as impaired cerebral blood flow (CBF) that result in prolonged impacts on brain function and quality of life in up to 15% of patients. We previously reported that nociceptin/orphanin FQ (N/OFQ) peptide (NOP) receptor antagonism revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 92 publications
3
6
1
Order By: Relevance
“…Though several previous TBI studies reported upregulation of the N/OFQ-NOP receptor system following TBI, none of them comprehensively examined protein, peptide, and mRNA level changes as a function of TBI severity [33,[35][36][37][38]. In this study, we report increases in N/OFQ levels in the injured brain tissue and CSF following mTBI and ModTBI on day 1 post-TBI in WT rats (Figure 2a,d).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Though several previous TBI studies reported upregulation of the N/OFQ-NOP receptor system following TBI, none of them comprehensively examined protein, peptide, and mRNA level changes as a function of TBI severity [33,[35][36][37][38]. In this study, we report increases in N/OFQ levels in the injured brain tissue and CSF following mTBI and ModTBI on day 1 post-TBI in WT rats (Figure 2a,d).…”
Section: Discussionmentioning
confidence: 50%
“…The nociceptin opioid peptide (NOP) receptor, part of the opioid receptor superfamily [21][22][23][24][25][26][27], and its endogenous neuropeptide, N/OFQ, are widely expressed in the human body, including neurons, astrocytes, and microglia [28,29]. Acute increases in N/OFQ levels were found in cerebrospinal fluid (CSF) shortly after fluid percussion injury (FPI) [30][31][32] and CCI [33]. N/OFQ vasodilates cortical pial arteries under normal conditions but produces vasoconstriction following FPI and CCI [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations